Systematic Literature Review : Kesulitan Siswa dalam Memahami Materi Pecahan pada Pembelajaran Matematika di Sekolah Dasar - Sukma Kurnia Syukra; Adrias Adrias; Salmaini Safitri Syam (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Understanding fraction concepts remains one of the biggest challenges in elementary mathematics education. Many students struggle with grasping fundamental fraction concepts, performing calculations, and applying them in problem-solving contexts. This study aims to analyze various factors contributing to students' difficulties in understanding fractions using a systematic approach Systematic Literature Review (SLR). Data were collected from relevant scholarly articles published between 2020 and 2025. The findings indicate that the primary difficulties students face in understanding fractions stem from a lack of conceptual comprehension, weak operational skills, and challenges in converting word problems into mathematical models. Additionally, low learning motivation and limited teaching method variations also contribute to students' struggles with fraction concepts.